Research Work Rating for the Faculty - M. M. Kudaev (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with specific rating of research work for the faculty and identifying internal components of research work and their decomposition with further distribution into duties and setting norms for each element of the structure in research or project. Current approaches to research work were studied and recommendations on its structure were given with due respect to digitalization. Based on the analysis of research work rating the author formulated an approach of splitting workers with regard to their individual qualities. The information base of the article was formed by normative and legal acts of the Russian Federation, state programs, data of the Federal Service of State Statistics, analytical reports, guiding materials and methodological recommendations, periodical economic publications, data of rating agencies, materials of conferences, official information dealing with work rating for the faculty of Russian universities and publications in mass media and the Internet. The author identifies theoretical and methodological approaches to developing the mechanism of work rating and regulating for the faculty on the basis of new principles of labour distribution aimed at raising labour productivity and quality of specialists’ training.